2022
DOI: 10.32604/cmc.2022.020017
|View full text |Cite
|
Sign up to set email alerts
|

Plant Disease Diagnosis and Image Classification Using Deep Learning

Abstract: Indian agriculture is striving to achieve sustainable intensification, the system aiming to increase agricultural yield per unit area without harming natural resources and the ecosystem. Modern farming employs technology to improve productivity. Early and accurate analysis and diagnosis of plant disease is very helpful in reducing plant diseases and improving plant health and food crop productivity. Plant disease experts are not available in remote areas thus there is a requirement of automatic low-cost, appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 38 publications
3
13
1
Order By: Relevance
“…Even the accuracy of the YOLO V5 model used by Mathew and Mahesh (2022) was 4.8% lower than our study. By comparing the model accuracy of the different number of disease categories, the model accuracy of Zhang et al (2020), Gao et al (2021), Sharma et al (2021), Zhao et al (2021), and Al-Wesabi et al ( 2022) is higher than our results, which is due to the smaller number of disease categories (up to 10 categories). Our study required the identification of up to 59 plant disease categories, which exceeded at least 85% of the disease categories in other studies and reduced the accuracy by up to 4.5% relative to other studies.…”
Section: Evaluation Of Model Trainingcontrasting
confidence: 86%
See 1 more Smart Citation
“…Even the accuracy of the YOLO V5 model used by Mathew and Mahesh (2022) was 4.8% lower than our study. By comparing the model accuracy of the different number of disease categories, the model accuracy of Zhang et al (2020), Gao et al (2021), Sharma et al (2021), Zhao et al (2021), and Al-Wesabi et al ( 2022) is higher than our results, which is due to the smaller number of disease categories (up to 10 categories). Our study required the identification of up to 59 plant disease categories, which exceeded at least 85% of the disease categories in other studies and reduced the accuracy by up to 4.5% relative to other studies.…”
Section: Evaluation Of Model Trainingcontrasting
confidence: 86%
“…Afzaal et al ( 2021 ) reported the studies obtained using classical convolutional neural networks, namely GoogleNet, VGGNet, and EfficientNet, to identify potato leaf diseases at different growth stages. Sharma et al ( 2021 ) proposed a CNN model for rice and potato leaf disease classification, which was able to classify rice images and potato leaves with 99.58% accuracy, outperforming other advanced machine learning image classifiers, such as SVM, KNN, decision trees, and random forests. To demonstrate the feasibility of deep learning algorithms based on an encoder-decoder architecture for semantic segmentation of potato late blight spots based on field images, Gao et al ( 2021 ) used a SegNet-based encoder-decoder neural network architecture for lesion segmentation, which can extract semantic features from low to high level, in a disease test dataset with leaves and soil in the background to intersect and union (IOU) values of 0.996 and 0.386, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The following are our main contributions to this study: − This study compares five machine learning models and five deep learning models to classify mint plant diseases in order to find the best classifier in the case of disease detection. − From literature reviews, various works reached that deep learning performed well in plant disease detection [9], [10]. Hence, this study proves and supports the previous works that DL is the best choice in analyzing the most important features affecting the detection and treatment of serious diseases versus ML since DL can perform feature extraction on its own.…”
Section: Introductionsupporting
confidence: 79%
“…Some scholars are devoted to the study of image feature extraction [1,2]. Feature extraction can be used for image classification [3,4], image segmentation [4][5][6][7], target detection [8][9][10][11], attention mechanism of the visual system [11][12][13][14][15][16] and other research directions. Images have individual features and common features, which are adversarial and interdependent in image recognition.…”
Section: Introductionmentioning
confidence: 99%